Effect of heat acclimatization, heat acclimation, and intermittent heat training on maximal oxygen uptake - Dunn, R. A.; Fry, L. A.; Sekiguchi, Y.; Benjamin, C. L.; Manning, C. N.; Huggins, R. A.; Stearns, R. L.; Casa, D. J. (Sports Health: A Multidisciplinary Approach, 2024)
Background; Maximal oxygen uptake (VO2max) is an important determinant of endurance performance. Heat acclimation/ acclimatization (HA/HAz) elicits improvements in endurance performance. Upon heat exposure reduction, intermittent heat training (IHT) may alleviate HA/HAz adaptation decay; however, corresponding VO2max responses are unknown.